Negative Cognitions Following Distressing Unwanted Sex: The Role of Coercion Severity and Perceived Consent - Kern, Sara G. (Journal of interpersonal violence, 2021)
Findings from past research suggest that unwanted sex (i.e., sex that is not fully desired) can result in a variety of outcomes, ranging from positive to negative. Some research has demonstrated that more severe coercion within unwanted sex is associated with more negative cognitions (particularly self-blame) following the unwanted sex, but findings are inconsistent. Previous research also has demonstrated that individuals’ perceptions of how much they consented to sex—regardless of the level of coercion—are associated with negative cognitions. In this study, we aimed to explore the potential moderating role of perceived consent in the relationship between sexual coercion severity and negative cognitions following unwanted sex. Participants (N = 196) who had had a distressing unwanted sexual experience provided descriptions of their most distressing experience, rated their perceptions of how much they consented to this experience, and completed a questionnaire measuring the amount and content of negative cognitions they experienced following this experience. Two independent raters coded descriptions to determine coercion severity. Results demonstrated that perceived consent significantly moderated the relationship between coercion severity and two types of negative cognitions: characterological self-blame and negative thoughts about the world. This suggests that individuals’ perceptions of their consent are often as important as the level of coercion involved in predicting cognitive outcomes of unwanted sex.